The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/nmo.13055
|View full text |Cite
|
Sign up to set email alerts
|

Low FODMAP in 2017: Lessons learned from clinical trials and mechanistic studies

Abstract: Given the prevalence of irritable bowel syndrome (IBS) and the suboptimal response to most therapeutic approaches, there has been increasing interest in and adoption of dietary treatment strategies, such as the low Fermentable Oligo-, Di-, & Mono-Saccharides and Polyols (FODMAP) diet. FODMAPs are a diverse group of carbohydrates that exert effects in the gastrointestinal tract not only via fermentation but likely via alterations in the microbiota, metabolome, permeability, and intestinal immunity as well. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…[110][111] Colonic hypersensitivity, rather than increased gas production and luminal distension, may drive the FODMAP-related symptoms in some IBS patients. 112 The study by Major et al 111 found that patients with IBS had symptomatic responses to inulin related to levels of intraluminal gas, but peak gas levels did not affect symptom response. This finding indicates that colonic hypersensitivity produces symptoms in patients with IBS rather than excessive gas production.…”
Section: Effect Of Fodmaps In the Gi Tract And The Low-fodmap Dietmentioning
confidence: 99%
“…[110][111] Colonic hypersensitivity, rather than increased gas production and luminal distension, may drive the FODMAP-related symptoms in some IBS patients. 112 The study by Major et al 111 found that patients with IBS had symptomatic responses to inulin related to levels of intraluminal gas, but peak gas levels did not affect symptom response. This finding indicates that colonic hypersensitivity produces symptoms in patients with IBS rather than excessive gas production.…”
Section: Effect Of Fodmaps In the Gi Tract And The Low-fodmap Dietmentioning
confidence: 99%
“…Fermentable Oligosaccharides, Disaccharides, Monosaccharides and Polyols (FODMAPs) are rapidly fermentable, poorly absorbed carbohydrates found in food that can cause digestive discomfort, especially for people with IBS [ 145 ]. The action of FODMAPS is likely via multiple pathways [ 146 ], and includes the release of gases from the bacterial fermentation of oligosaccharides and the proportion (if any) of malabsorbed fructose, polyols, and lactose [ 147 ]. Symptoms associated with FODMAPs include abdominal bloating, pain, cramps, excessive flatulence and altered bowel habit [ 146 ].…”
Section: Digestive Healthmentioning
confidence: 99%
“…FODMAPs include foodstuffs that contain fructose (apples, pears, watermelon and honey), vegetables rich in fructan (onions, asparagus, artichoke and leek), wheat-based products (bread, doughs in general), sorbitol (artificial sweeteners) and raffinose (cabbage, lentils and beans). Although highly restrictive, a FODMAP free diet generally brings notable benefits to IBS patients (8,9,16,19,23,29,30) . All foods in the questionnaire were reported as domestic measures converted into grams, using the table set out by the Department of Nutrition at the Federal University of Rio de Janeiro (36) , consumption patterns were recorded for one month and was applied by the interviewer.…”
Section: Figure 1 Relation Between Fodmaps and Functional Intestinalmentioning
confidence: 99%